Development of Nanoemulsions for Topical Application of Mupirocin - Bahjat Alhasso; Muhammad Usman Ghori; Barbara R. Conway (MDPI AG, 2023)
Mupirocin (MUP) is a topical antibacterial agent used to treat superficial skin infections but has limited application due to in vivo inactivation and plasma protein binding. A nanoemulsion formulation has the potential to enhance the delivery of mupirocin into the skin. MUP-loaded nanoemulsions were prepared using eucalyptus oil (EO) or eucalyptol (EU), Tween® 80 (T80) and Span® 80 (S80) as oil phase (O), surfactant (S) and cosurfactant (CoS). The nanoemulsions were characterised and their potential to enhance delivery was assessed using an in vitro skin model. Optimised nanoemulsion formulations were prepared based on EO (MUP-NE EO) and EU (MUP-NE EU) separately. MUP-NE EO had a smaller size with mean droplet diameter of 35.89 ± 0.68 nm and narrower particle size index (PDI) 0.10 ± 0.02 nm compared to MUP-NE EU. Both nanoemulsion formulations were stable at 25 °C for three months with the ability to enhance the transdermal permeation of MUP as compared to the control, Bactroban® cream. Inclusion of EU led to a two-fold increase in permeation of MUP compared to the control, while EO increased the percentage by 48% compared to the control. Additionally, more MUP was detected in the skin after 8 h following MUP-NE EU application, although MUP deposition from MUP-NE EO was higher after 24 h. It may be possible, through choice of essential oil to design nanoformulations for both acute and prophylactic management of topical infections.